Karakteristik Mutu Garam Fungsional Tanaman Alur (Suaeda maritima) Berdasarkan Perbandingan Rasio Pelarut dan Tepung Alur - Nabilah, Ana; Maflahah, Iffan; Supriyanto, Supriyanto; Asfan, Dian Farida (Universitas Trunojoyo Madura, 2024)
Seablite (Suaeda maritimea) is a plant that grows in salt marshes and furrow soil which is rich in vitamin A content. Seablite is one of the plants that can be used as functional raw materials. Functional salts are salts that have a low NaCl content (less than 50%). The purpose of this study was to determine the effect of the ratio of air and seablite flour on the quality of the functional salt of the seablite. The characteristics of the salt used were moisture content test, ash content, salinity test, NaCl test, and vitamin A test. Salt was prepared by air treatment and seablite t flour, namely 1:5, 1:10, 1:15 and 1: 20. The technique of making seablitefunctional salt is to start by dissolving the seablite flour with water as a solvent. Heating the solution for 10 minutes, filtering using a filter cloth, the resulting filtrate is then deposited for 3 days, the precipitate from the seablite flour solution is then dried for 3 days at a temperature of 65oC, finally weighing the material in the form of seablite plant salt. Based on the results of the quality characteristic research, the difference in the ratio of the solvent ratio to the seablite flour gives a significant difference to the quality characteristics of the functional salt of the seablite plant, the analysis of theyield, water content, ash content, salinity, NaCl content and vitamin A content.